Obesity and functional constipation in children - Natasha Yuwanita; Atan Baas Sinuhaji; Tiangsa Sembiring; Supriatmo Supriatmo; Ade Rachmat Yudiyanto (Paediatrica Indonesiana, 2018)
Background Functional constipation is a common pediatric problem in both developed and developing countries. In the past two decades, the prevalence of obesity has increased worldwide. Obesity itself leads to many health problems, including functional constipation. Studies correlating obesity to functional constipation have thus far mostly originated from developed countries. Objective To assess for a possible correlation between obesity and functional constipation in children in a developing country. Methods This cross-sectional study was conducted in Al-Mukhlisin Islamic Boarding School, Batu Bara District, North Sumatera Province, Indonesia, between July and August 2015. The subjects were 150 students aged 12 to 17 years. Questionnaires were used to determine functional constipation and filled by direct interview. Obesity was determined by body mass index. Data were analyzed using Chi-square test. Results Of 150 children, 49 had functional constipation; and 18 of the 49 were obese. The mean age of children with constipation was 14.7 (SD 1.07) years (95%CI 14.1 to 14.7) and their mean body weight was 53.8 (SD 15.10) kg (95%CI 49.4 to 58.1). The prevalence for functional constipation in obese children was Â 58% There was a statistically significant correlation between obesity and functional constipation (prevalence ratio=4; 95%CI 1.72 to 8.94; P=0.001), indicating that obese children had 4 times higher risk of having functional constipation. Conclusion There is a significant correlation between obesity and functional constipation in children.